(3Odjd dQDSGA GdCbSGe hGdYeOGAs - (3OQjd BQ(B, (3dejfZs; (3aGVd(B, (3LJcQs ((3GdQjGV(B:s (3ecJHI GdYHjcGJ ddfTQ hGdJhRjY(B,s, 2006)
(3CYQa faSc,age GdBNQjf hGdJhGUd eYge,OaY GdgjFI GdJOQjSjI Edi GdJhGab,JhXja GdELJeGYGJ dJMbjb GdJeGSc,cSH GdeYGQVjf,GdJYGed eY gjFI JOQjSjI eQJHcI,GSJNOGe GdJbhje COGI dJMSjf COGA GdgjFI GdJOQjSjI hcSH QVGgG,de LejY GdNjhW hUhdG Edi Cf jUHM GdeQA eOjQG hbGFOG CaVds
(3HHdjhZQGajG(B:(3U(B.335-348s
Keywords: (3GOGQI GdGaQGOs